2011
DOI: 10.1105/tpc.110.074005
|View full text |Cite
|
Sign up to set email alerts
|

The PP2A Regulatory Subunit Tap46, a Component of the TOR Signaling Pathway, Modulates Growth and Metabolism in Plants

Abstract: Tap42/α4, a regulatory subunit of protein phosphatase 2A, is a downstream effector of the target of rapamycin (TOR) protein kinase, which regulates cell growth in coordination with nutrient and environmental conditions in yeast and mammals. In this study, we characterized the functions and phosphatase regulation of plant Tap46. Depletion of Tap46 resulted in growth arrest and acute plant death with morphological markers of programmed cell death. Tap46 interacted with PP2A and PP2A-like phosphatases PP4 and PP6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
197
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(211 citation statements)
references
References 94 publications
5
197
1
8
Order By: Relevance
“…Depletion of Tap46 reproduced the signature phenotypes of TOR inactivation, including autophagy induction. 30 …”
Section: Autophagy In Plantsmentioning
confidence: 99%
“…Depletion of Tap46 reproduced the signature phenotypes of TOR inactivation, including autophagy induction. 30 …”
Section: Autophagy In Plantsmentioning
confidence: 99%
“…For Gle1(C) RNAi lines, a 330-bp Gle1 cDNA fragment was amplified by PCR using 59-CACAAAGCTTGCATTTACACT-39 and 59-ATGCTCTCTCACAACATTCAC-39 primers containing XhoI and ClaI sites for the sense construct, and SpeI and BamHI sites for the antisense construct. Using these constructs, DEX-inducible Gle1 RNAi Arabidopsis lines were generated as described (Ahn et al, 2011). For induction of RNAi, the transgenic seedlings were grown on medium containing 10 mM DEX in ethanol (0.033%).…”
Section: Generation Of Arabidopsis Dex-inducible Gle1 Rnai Linesmentioning
confidence: 99%
“…VIGS was performed in N. benthamiana as described (Lee et al, 2009;Ahn et al, 2011;Cho et al, 2013).…”
Section: Vigsmentioning
confidence: 99%
“…In Arabidopsis, the TON2/FASS is the only B (a B'') regulatory subunit that has been firmly characterized so far, and was found to be involved in cortical microtubule organization and important for cell shape (Camilleri et al, 2002;Wang et al, 2007). Very recently it was shown that silencing of TAP46 in Arabidopsis, the ortholog of the yeast TAP42 protein, a PP2A catalytic subunit interacting protein, affects NR expression (Ahn et al, 2011). When we tested different B subunits for interaction with NR, positive results were found for the B55 group.…”
mentioning
confidence: 99%